Martin Luther King’s Reaction to the Cuban Missile Crisis - Leonardo Campus (European Journal of American Studies)
This research article deals for the first time with the reaction of Martin Luther King Jr. to the Cuban missile crisis of October 1962. In doing so, it also presents a document of special relevance: the draft of a previously-unknown private letter from dr. King to President Kennedy, in which the civil rights leader praised Kennedy’s management of that crucial nuclear confrontation between US and USSR and saw in it the potential for détente. The paper reflects on the elements currently available for the interpretation of this piece of evidence and, with regard to the relationship between the two leaders, it argues that the way Kennedy handled the Cuban crisis may well have played a role in Dr. King’s reassessment of Kennedy’s evolving qualities of leadership - a view that King will further develop over the course of 1963 (in the most fruitful months of their cooperation) and will express after Dallas.